2018
DOI: 10.1155/2018/6104169
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Alpha-Tocopherol and Retinol with the Extent of Coronary Lesions in Coronary Artery Disease

Abstract: Background and aims: Fat-soluble vitamins play an important role in the pathogenesis of cardiovascular disease and progression of atherosclerosis. This study aimed at investigating the relationship of the serum levels of alpha-tocopherol and retinol with the extent of coronary lesions in patients with coronary artery disease. Methods. Patients with coronary artery disease (n=177) aged 30–74 years, who underwent their first coronary angiography, were enrolled. The extent of coronary lesions was assessed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
2
3
0
1
Order By: Relevance
“…Alpha tocopherol levels were observed to increase in the present study in the kidney tissue of diabetic rats (Table 3). In accordance with previous studies, increased levels of alpha tocopherol have been reported in the tissue of diabetic rats (Miranda et al., 2018; Miyazaki et al., 2013). The accumulation of retinol and alpha tocopherol in the kidney tissue of diabetic rats may have been decreased due to the beneficial effects of CUR and C60 on glucose metabolism.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Alpha tocopherol levels were observed to increase in the present study in the kidney tissue of diabetic rats (Table 3). In accordance with previous studies, increased levels of alpha tocopherol have been reported in the tissue of diabetic rats (Miranda et al., 2018; Miyazaki et al., 2013). The accumulation of retinol and alpha tocopherol in the kidney tissue of diabetic rats may have been decreased due to the beneficial effects of CUR and C60 on glucose metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…Previous diabetes studies have reported increased levels of α‐tocopherol in plasma and liver tissue. Oxidative stress is able to regulate α‐TTP transcription upward (Miranda et al., 2018; Miyazaki et al., 2013). It has been announced that hyperglycemia, or insulin resistance, can lead to increase a‐tocopherol levels by regulating α‐TTP gene expression (Arulselvan & Subramanian, 2007; Miyazaki et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A deficiency of β-carotene was particularly significant in our study. In the studies of Miranda et al [ 47 ], on the relationship between the severity of ischemic heart disease and plasma vitamin levels, a deficiency of α-tocopherol and retinol was found in some patients. In contrast, lower concentrations of these vitamins were observed in patients at the initial stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The control group came from the database of a previous study by our research group [23], consisting of participants recruited from a hemodynamics unit, selected for undergoing their first coronary angiography; however, only those who obtained a negative result for the diagnosis of coronary arterial disease were selected. In addition, none of these participants had any condition that affected vitamin A levels or could cause conflicts regarding the analysis of retinol for comparative purposes.…”
Section: Data Collection and Characterization Of The Populationmentioning
confidence: 99%